2014
DOI: 10.1130/g35808.1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid magma evolution constrained by zircon petrochronology and 40Ar/39Ar sanidine ages for the Huckleberry Ridge Tuff, Yellowstone, USA

Abstract: Understanding the time scales of magmatic differentiation, storage, and eruption of largevolume silicic magmas is a primary goal of igneous petrology. Within the Huckleberry Ridge Tuff (HRT; Idaho, USA), representing the earliest and largest caldera-forming eruption associated with Yellowstone volcanic activity, zircon morphological zoning patterns coupled to strongly correlated changes in Ti-in-zircon thermometry and trace element indicators of progressive differentiation provide a proxy record for the evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 26 publications
7
75
0
Order By: Relevance
“…7). Four concordant plateaus ranging in age from 2.084 ± 0.005/0.006 to 2.097 ± 0.004/0.006 Ma were generated from what we interpret to be antecrysts, thereby confirming the observations of Rivera et al (2014) and Gansecki et al (1998), but at a scale that the latter study could not resolve owing to large single-crystal uncertainties. is in excess of the single data point uncertainties which range from 10.4 to 96.6 kyr (2σ ) (Fig.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…7). Four concordant plateaus ranging in age from 2.084 ± 0.005/0.006 to 2.097 ± 0.004/0.006 Ma were generated from what we interpret to be antecrysts, thereby confirming the observations of Rivera et al (2014) and Gansecki et al (1998), but at a scale that the latter study could not resolve owing to large single-crystal uncertainties. is in excess of the single data point uncertainties which range from 10.4 to 96.6 kyr (2σ ) (Fig.…”
Section: Resultssupporting
confidence: 67%
“…Lanphere et al (2002) suggested that there is a small amount of excess Ar present in HRT sanidine, which results in total fusion ages that are older than the eruption age. Rivera et al (2014) suggest that sanidine and Ages calculated relative to 28.201 Ma Fish Canyon sanidine (Kuiper et al, 2008) using decay constants of Min et al (2000). Preferred age for each sample is given in bold font.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The consistency between U -Pb and astronomical dating has been substantiated by single crystal U -Pb zircon dating of several ash layers in the tuned Monte dei Corvi and La Vedova sections of northern Italy (Wotzlaw et al 2014). Single crystal 40 Ar/ 39 Ar dating of Pleistocene silicic volcanics that incorporate an astronomically calibrated age of the FCs neutron fluence monitor yield eruption ages that achieve concordance or near concordance with CA-ID-TIMS 238 U/ 206 Pb zircon latecrystallization dates (Rivera et al 2013(Rivera et al , 2014Singer 2014). The use of these (or similar) radio-isotopic dating methods also nears or achieves concordance with independently determined astronomical ages for the same units, extending from the Pleistocene to the Cretaceous (Smith et al 2010;Meyers et al 2012;Wu et al 2013a;Ma et al 2014;Sageman et al 2014).…”
mentioning
confidence: 87%